Analisis Buku Bahasa Arab untuk Siswa Tingkat Madrasah Aliyah Terbitan Kemenag Tahun 2020 - Meliana Robiatulmahmudah; Yulva Maya Padilah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to analyze the feasibility of Arabic textbooks for Madrasah Aliyah (Islamic Senior High School) published by the Ministry of Religious Affairs (Kemenag) in 2020 as teaching materials based on the standards of the National Education Standards Agency (BSNP). This library research employs content analysis to evaluate the feasibility of content, presentation, language, and graphics of the three books (grades X, XI, XII) adapted to KMA 183 of 2019. The results indicate shortcomings in the accuracy of illustrations (general), completeness of material (grade X), grammatical errors (grade XII), balance of material per chapter, completeness of presentation support, errors in diacritics syakal in idhofah and na’at man’ut constructions, and cover design and illustrations that are less proportional and difficult to interpret. This research recommends improvements to these aspects to enhance the quality of Arabic textbooks.